Histological Structure of the Plastinated Kidney Following Deplastination - Baygeldı, Saıme Betül; Seker, Ugur; Güzel, Barış Can (My University, 2022)
Plastination is a laboratory process to obtain permanent dry tissue and organ sample. That can be used in the future for investigation and educational purposes. This methodology is based on dehydration and penetration of synthetic substances such as silicon into tissue. In this study, it was aimed to deplastinate previously plastinated kidneys in order to examine them under the light microscope. In this study, 14 sheep kidneys were used, seven samples of control and seven samples of plastination-deplastination (p / d) group. Kidneys in both control and p/d groups were fixed in 10% formalin. The samples in the control group were embedded in paraffin following routine tissue processing protocol. However, the samples in the p/d group were deplastinated in alcohol and methylbenzene and embedded into paraffin. 5 ?m thick sections obtained from paraffin blocks were stained with hematoxylin and eosin (H&E), periodic acid-shiff (PAS) and then examined under the light microscope. Typical histological structures were observed in the control group. Small fragments were obtained as it was challenging to obtain sections from the P/d group blocks. Morphological structures were visible with some pseudo degenerations and wrong staining. This study is the first study that demonstrates alcohol and methylbenzene deplastination can be partially successful for evaluating plastinated kidney samples under a light microscope. However, we believe that the kidney may have limitations due to its wide parenchyma compared with literature conclusions. Nevertheless, more studies are required to develop the optimum protocols.
Keywords: Sheep; histology; Kidney; plastination; veterinary anatomy